Some useful weeds from Ahemadnagar district , Maharashtra, India - Mulay, J R; Sharma, P P (International Multidisciplinary Research Journal, 2013)
Traditional knowledge has assumed great importance in enhancing our knowledge about the plants which are used by the people since time immemorial. During last few decades, sufficient research work on ethnobotany has been done in various parts of India by various workers. However, Ahemednagar district have not been given enough attention as far as ethnobotanical studies are concerned. Hence, to fill up the gap the present investigation has been undertaken. Total 30 weed species belongs to 18 families are recorded, while common diseases/ailments for which most of the plants used are Joint pains (7 species), Warts and wound (5 species) Headache, Tonic and cough (4 species each), Jaundice (3).